Prophage-mediated endolysis of Latilactobacillus Sakei TMW 1.1290 induced by exogenous stress arising from food technologies - T Bardischewski; S Vallo; R Nitzsche; P Chanos; T Sieksmeyer; C Stühmeier-Niehe; K Aganovic; C Hertel (BMC Microbiology)
Abstract Background Intracellular enzymes released during bacterial cell lysis contribute to the development of flavor and texture in fermented foods through the hydrolysis of proteins and fats. In fermented meat products this takes place only late in the fermentation process which limits its effect. Therefore, time-controlled cell lysis constitutes a potentially valuable tool for enhancing sensory characteristics of the final product. This study investigated the prophage-induced, time-delayed bacterial cell lysis in L. sakei TMW 1.1290 by using different stress conditions, including those generated by food technologies, like pulsed electric fields (PEF) and high hydrostatic pressure (HHP). Results UV light induced transient cell lysis, confirmed by a 2102-fold increase of expression of the prophage amidase gene, as determined by Reverse Transcription quantitative Polymerase Chain Reaction (RT-qPCR). The effect of oxidative stress chemicals like menadione and hydrogen peroxide was far more pronounced, causing evident cell lysis, although probably differing in their modes of action. Although PEF treatment and HHP are known to cause direct or indirect oxidative stress in cells, their applications on cell suspensions at sublethal conditions were not able to cause cell lysis induction under the experimental conditions used. Conclusions Prophage-mediated cell lysis in L. sakei TMW 1.1290 can be induced by UV light and mitomycin C, while H₂O₂ and menadione showed prophage activation potential but significantly inhibited growth. Food technologies like PEF and HHP were ineffective at inducing prophage-mediated cell lysis despite causing sublethal injury, requiring further study of treatment parameters.